Research Exceptionalism - Wilson, James; Hunter, David (American journal of bioethics, 2010)
Research involving human subjects is much more stringently regulated than many other nonresearch activities that appear to be at least as risky. A number of prominent figures now argue that research is overregulated. We argue that the reasons typically offered to justify the present system of research regulation fail to show that research should be subject to more stringent regulation than other equally risky activities. However, there are three often overlooked reasons for thinking that research should be treated as a special case. First, research typically involves the imposition of risk on people who do not benefit from this risk imposition. Second, research depends on public trust. Third, the complexity of the moral decision making required favors ethics committees as a regulative solution for research.